2015
DOI: 10.1177/0014402915585478
|View full text |Cite
|
Sign up to set email alerts
|

Improving Reading Comprehension for High School Students With Disabilities

Abstract: The authors examine the results for students with disabilities from a 2-year randomized controlled trial with students identified in ninth grade and followed through 10th grade in their allotted condition group. Prior to ninth grade, students with disabilities who met criteria for low reading comprehension (i.e., through failure on the state accountability test) were randomly assigned to one of three treatment conditions-reading without dropout prevention, reading with dropout prevention, dropout prevention wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…Traditionally, students with disabilities score poorer than their peers without disabilities on vocabulary, as well as reading comprehension, measures (Leko, Alzahrani, Handi, 2019;Vaughn et al, 2015). As recently as 2015, based on findings from the NCES, Average Scale Score for Reading in which reading scale scores range from 0-500, students without disabilities averaged a 269-scaled score while students with disabilities average score was a 226.…”
Section: Implications For Students With Disabilitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Traditionally, students with disabilities score poorer than their peers without disabilities on vocabulary, as well as reading comprehension, measures (Leko, Alzahrani, Handi, 2019;Vaughn et al, 2015). As recently as 2015, based on findings from the NCES, Average Scale Score for Reading in which reading scale scores range from 0-500, students without disabilities averaged a 269-scaled score while students with disabilities average score was a 226.…”
Section: Implications For Students With Disabilitiesmentioning
confidence: 99%
“…In fact, Kuder (2017) most recently states that a review of the current literature shows that of the five most common types of intervention, (fluency, word study, vocabulary, comprehension, multi-component methods), vocabulary instruction produces the largest effect size (1.62) thus indicating improvement in this isolated skill continues to be critical area for instruction. Vaughn et al (2015) states that as students' age, vocabulary knowledge and reading difficulties become compounded. In a study of 9 th grade students, Lang et al (2009) found that these students require greater support and interventions to improve their deficits in both background knowledge and vocabulary for meaning to occur.…”
Section: Implications For Students With Disabilitiesmentioning
confidence: 99%
See 3 more Smart Citations